Analysis of The Influence of Virtual Travel Services and Digital Information on Tourists Behavior in Determining Destinations - Hendra; Akhirianto, Pas Mahyu; Widia Nurdiani, Tanti; Bawaiqki Wandanaya, Anita (Jurnal Sistim Informasi dan Teknologi, 2024)
This research aims to study the influence of information media and virtual travel agents on consumer decisions when booking tourist accommodations. This research uses a qualitative approach. Information collection methods include user diaries, focus groups, and open interviews. According to the analysis, millennial consumers choose accommodation based on functional factors such as price, location, cleanliness, service, and facilities, but we also pay attention to community aspects such as shared spaces. This research tends to use information media and online travel agencies as well as trust reviews from strangers on the web. Online social influences, particularly other users' comments and evaluations, have a significant impact on their decisions. Therefore, accommodation providers need to pay attention to their reputation and consumer reviews. Photos of accommodation are also important in forming consumer perceptions, although they may not always reflect reality. Developing a marketing strategy that emphasizes price, facility, and service advantages, as well as understanding the needs of millennial consumers, will help increase the hotel industry's attractiveness in today's competitive market.